KAJIAN TATANAN DAKWAH TERHADAP PERAN SISTEM DAKWAH SEBAGAI SUBSISTEM SOSIOKULTURAL, IDEOLOGI DAN POLITIK - Muhammad Aris Fachrizal; Heluny Otistaviany; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The da'wah system has become an integral part of society which has a strong ideological and political foundation. As a sociocultural subsystem, its role in shaping and influencing the ideology and politics of a society is very important. This article aims to provide an in-depth review of how the da'wah system acts as a sociocultural subsystem that has an impact on ideology and politics. This research aims to analyze the role of the da'wah system as a sociocultural subsystem in ideological and political dynamics. The method used is library research, which involves analysis of various literature, articles and related information sources. The findings from this research show that the da'wah system has a significant role in shaping and influencing ideology and politics in society. The da'wah system functions as an agent of social change that influences the values, beliefs, and political actions of individuals and groups. Through a library research approach, this research provides in-depth insight into how the da'wah system plays a crucial role in directing ideological and political flows in a social and cultural context.